Menggunakan Aplikasi Vosviewer untuk Analisis Penilaian Pembelajaran Fisika - Patty, Elyakim Nova Supriyedi; Iriyani, Sri Astuti; Irhas, Irhas; Suluh, Melkianus (CT. Rajawali media Utama, 2023)
To improve the quality of learning outcomes, there is a need for studies that write about physics learning assessment in the form of high order thinking skill assessment, project-based, cognitive assessment and psychomotor assessment. The purpose of this study is to systematically analyze and demonstrate step-by-step bibliometric data analysis using VOSViewer. A step-by-step tutorial is provided to make VOSViewers easier to use for first-time users. Thus, physics learning assessment can be integrated with other fields of study. This study presents data analysis related to physics learning assessment for a decade (2013-2022) using the mapping tool in VOSViewer. The method used is descriptive and qualitative to detail the performance of bibliometric analysis by creating network visualizations of selected topics. From the search results, 993 relevant journals published in 2013-2022 were found, which were then divided into 10 categories based on the year of publication. After analyzing the journal data, we found that the largest number of articles were published in 2016-2018. There are many ways to discover new things about this topic. This review is intended as a guideline for teachers/lecturers in using learning assessment and for authors conducting research and identifying future research topics.